2005
DOI: 10.1097/01.alc.0000156185.39073.d2
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Acetaldehyde in the Central Effects of Ethanol

Abstract: This article represents the proceedings of a symposium at the 2004 annual meeting of the Research Society on Alcoholism in Vancouver, Canada. The symposium was organized by Etienne Quertemont and chaired by Kathleen A. Grant. The presentations were (1) Behavioral stimulant effects of intracranial injections of ethanol and acetaldehyde in rats, by Mercè Correa, Maria N. Arizzi and John D. Salamone; (2) Behavioral characterization of acetaldehyde in mice, by Etienne Quertemont and Sophie Tambour; (3) Role of bra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(46 citation statements)
references
References 82 publications
(128 reference statements)
1
45
0
Order By: Relevance
“…Originally, it was postulated that peripheral ACD was unlikely to enter the CNS due to the prevalence of ALDH and the blood-brain barrier (Hunt, 1996). Further research indicated that high levels of peripherally administered ACD results in detection of ACD in the brain within minutes (Ward et al, 1997) Therefore, peripheral ACD may overwhelm the peripheral ALDH, allowing some percentage of ACD to enter the brain (Quertemont et al, 2005). Additional local metabolic pathways (e.g.…”
Section: Acetaldehyde Production In Cnsmentioning
confidence: 99%
“…Originally, it was postulated that peripheral ACD was unlikely to enter the CNS due to the prevalence of ALDH and the blood-brain barrier (Hunt, 1996). Further research indicated that high levels of peripherally administered ACD results in detection of ACD in the brain within minutes (Ward et al, 1997) Therefore, peripheral ACD may overwhelm the peripheral ALDH, allowing some percentage of ACD to enter the brain (Quertemont et al, 2005). Additional local metabolic pathways (e.g.…”
Section: Acetaldehyde Production In Cnsmentioning
confidence: 99%
“…There is also extensive indirect evidence that AcH is responsible for a portion of the acute CNS effects of EtOH [reviewed in [13][14][15][16]17]. The issue addressed in this review is whether or not AcH may also play a role in tolerance and dependence of EtOH, hallmarks of "addiction".…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that some of the behavioral effects of ethanol are mediated by the first ethanol metabolite, acetaldehyde (Hunt 1996;Smith et al 1997;Quertemont et al 2005). Data suggesting a psychopharmacological significance for this ethanol metabolite was derived from two different approaches.…”
Section: Introductionmentioning
confidence: 99%